ANALISIS TINGKAT KEBERHASILAN SEKOLAH TERHADAP PENERAPAN PEMBELAJARAN BLENDED LEARNING DI MTs NUR- ATTAQWA KELAPA GADING, JAKARTA UTARA - Azmy Ali Muchtar (Ilma Jurnal Pendidikan Islam, 2022)
Globalization brings major changes in all sectors, the current era is known as the era of society 5.0 where people can solve all kinds of challenges and problems by utilizing various kinds of innovative technologies that have been created in the era of the industrial revolution 4.0. no exception in the world of education, the learning process that was originally usually held in the classroom must change to online learning and can also be done by uniting the two, namely offline and online or known as blended learning. This form of learning can provide flexibility for students to learn efficiently and effectively and can make it easier to understand the subject matter because learning activities are a combination of online and offline learning (face to face). The results of this study indicate that the average percentage of answers to the questionnaire with respondents agreeing with the implementation of the blended learning model in schools is 65.5 with the highest score at point 5 of 75.6%, which means that blended learning allows students to get feedback faster, can attract the attention of students and the use of blended learning can improve student learning outcomes.